PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE TERHADAP HASIL BELAJAR PASING BAWAH BOLAVOLI (STUDI PADA SISWA KELAS V SDN SINGOWANGI MOJOKERTO) - ISWANTO, YUDHA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Physical education is a form of education which uses body movement as a mean and the purpose of education. Through physical education, students are directed to the physical activities including sports ability, one of them is the learning process of underhand pass in volley ball. Based on that matter, the increasing of teaching-learning in physical education at school is needed and the innovation in teaching-learning model which can coop with that problem is also needed Based on that matter, the researcher is formulating some problems which are whether there is effect and how big is the effect of applying cooperative learning model, Think-Pair-Share, on the learning result of underhand pass volley ball at the students of eighth grade students  of  SDN Singowangi subdistrict Kutorejo or not. The aim of this research is to know the effect and how big is the effect of applying cooperative learning model, Think-Pair-Share, on the learning result of underhand pass volley ball at the students of eighth grade students  of of SDN Singowangi subdistrict Kutorejo Mojokerto. This research is an experimental study with using descriptive quantitative approach. Experimental study is a research conducted tightly to find out cause-effect relationship between variables. One of the main characteristics is the existence of treatments given to the subject. in this research, the researcher uses one group pre-test post-test design. The population which is used by the researcher is the eighth grade students  of SDN Singowangi Kecamatan Kutorejo Mojokerto consist of six classes which have 242 students.  the sample of this research is the students in class V consitc of 38 student. The application cooperative learning model, Think-Pair-Share to see value t greater than t table, Hence, it can be concluded that there Ha acceptance and Ho a push away, because value t greater 13,062 > value t table 1,684. The rate of improvement for the researcher sample and after the cooperative learning model, Think-Pair-Share applied is 23,65%. Hence, it can be concluded that there is significant influence between the implementation of cooperative learning model type think-pair-share and the learning improvement in volley ball down-pass on the eighth grade students  of class V SDN singowangi kecamatan  Kutorejo Mojokerto. Keywords: cooperative learning model, think-pair-share, the learning result of underhand pass volley ball.